Miljökemikaliers påverkan på isbjörnars (Ursus maritimus) reproduktion och hur dessa kemikalier når djuren - Isaksson, Jessica (2015)
Environmental chemicals are transported to the Arctic through the air and oceans, once within the Arctic they spread through rivers, lakes and other watercourses. Polar bears and sledge dogs in-gest high concentrations of environmental chemicals since many of the chemicals are fat-soluble and their diet mainly consists of marine mammals. The aim of this study is to describe how environmental chemicals spread in nature, how they reach the polar bears, and finally how they affect the animals reproduction, with reproductive hormones and genitals in focus. The animals are exposed to a cocktail effect which complicates the assessment of the chemicals impact on the reproduction. Studies show that the genitals can decrease in size or become malformed, sexual maturation can be affected and the reproductive hormones can be disturbed. This can complicate or delay courtship, mating and gestation. More research is needed in this area to get a better picture of how the polar bears reproduction is affected and to understand how environmental chemicals may affect the survival of the species in the future. It is also important to extend the research so more environmental chemicals are included, because of the complexity of the cocktail effect.